Physical Activity Patterns Among Latinos in the United States: Putting the Pieces Together - Sandra A. Ham, MS; Michelle M. Yore, MPH; Judy Kruger, PhD; Gregory W. Heath, DHSc, MPH; Refilwe Moeti, MA (Centers for Disease Control and Prevention, 2007)
IntroductionEstimates of participation in physical activity among Latinos are inconsistent across studies. To obtain better estimates and examine possible reasons for inconsistencies, we assessed 1) patterns of participation in various categories of physical activity among Latino adults, 2) changes in their activity patterns with acculturation, and 3) variations in their activity patterns by region of origin.MethodsUsing data from four national surveillance systems (the National Health and Nutrition Examination Survey, 1999-2002; the Behavioral Risk Factor Surveillance System, 2003; the National Household Travel Survey, 2001; and the National Health Interview Survey Cancer Supplement, 2000), we estimated the percentage of Latinos who participated at least once per week in leisure-time, household, occupational, or transportation-related physical activity, as well as in an active pattern of usual daily activity. We reported prevalences by acculturation measures and region of origin.ResultsThe percentage of Latinos who participated in the various types of physical activity ranged from 28.7% for having an active level of usual daily activity (usually walking most of the day and usually carrying or lifting objects) to 42.8% for participating in leisure-time physical activity at least once per week. The percentage who participated in leisure-time and household activities increased with acculturation, whereas the percentage who participated in occupational and transportation-related activities decreased with acculturation. Participation in an active level of usual daily activity did not change significantly. The prevalence of participation in transportation-related physical activity and of an active level of usual daily activity among Latino immigrants varied by region of origin.ConclusionPhysical activity patterns among Latinos vary with acculturation and region of origin. To assess physical activity levels in Latino communities, researchers should measure all types of physical activity and the effects of acculturation on each type of activity.